Graphic design : 2 the application of good design. (Northfield, IL : Goldsholl Learning Videos, a division of Goldsholl Design & Film Inc., 1989)
Corporate graphics and multi-element projects are shown from preliminary explorations to comphrensives and final print pieces. Computer design techniques are also demonstrated.
VHS format.
Keywords: Graphic arts -- Techique; Computer drawing